Implementation of Prenatal Yoga to Relieve Low Back Pain in Pregnant Women - Kumalasari, Retno; Maesaroh, Maesaroh; Isnaeni, Siti; Widiastuti, Fransisca (Ahmar Metastasis Health Journal, 2024)
Feeling comfortable during pregnancy improves overall quality of life. Pregnant women who feel comfortable are better able to enjoy their pregnancy, participate in social activities, and maintain positive relationships with their partners and families. The physical and hormonal changes that pregnant women experience cause discomfort, such as low back pain, which pregnant women commonly experience. Managing low back pain during pregnancy can prevent long-term musculoskeletal problems. Yoga exercises for pregnant women have many benefits, one of which is to overcome low back pain that is often experienced during pregnancy. This study aims to describe prenatal yoga is effective in relieving low back pain in pregnant women. This study used a Quasy Experiment research design using an equivalent time sample design model. The population of pregnant women in this study were pregnant women TM II and III who made visits who made ANC visits at the Independent Practice of Midwife Nurhikmah Hildayanti Cirebon Regency. The sampling method in this study was non probability sampling similar to consecutive sampling. Data collection was carried out using an observation sheet, by recording the level of decrease in the intensity of low back pain, after the intervention was carried out to reduce the intensity of low back pain by doing pregnant gymnastics and yoga. The results showed a decrease in the intensity of low back pain experienced by respondents after prenatal yoga was done both at the first meeting to the fourth meeting. The application of prenatal yoga carried out in the Independent Practice of Midwife Nurhikmah Hildayanti Cirebon Regency can relieve low back pain in pregnant women TM II and III.